The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2807/1560-7917.es.2022.27.9.2100419
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of IgG antibodies against SARS-CoV-2 – a serial prospective cross-sectional nationwide study of residual samples, Belgium, March to October 2020

Abstract: Background To control epidemic waves, it is important to know the susceptibility to SARS-CoV-2 and its evolution over time in relation to the control measures taken. Aim To assess the evolving SARS-CoV-2 seroprevalence and seroincidence related to the first national lockdown in Belgium, we performed a nationwide seroprevalence study, stratified by age, sex and region using 3,000–4,000 residual samples during seven periods bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Incomplete case-finding prior to and over the study period however remains a possible bias for our VE-estimates. Despite high capacity and free RT-PCR-tests, Belgian seroprevalence studies report underdiagnosis of SARS-CoV-2-infections [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete case-finding prior to and over the study period however remains a possible bias for our VE-estimates. Despite high capacity and free RT-PCR-tests, Belgian seroprevalence studies report underdiagnosis of SARS-CoV-2-infections [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Results from the SalivaHIS study, conducted when the vaccination campaign in Belgium was running at full speed (between March and August 2021), found that the prevalence of anti-SARS-CoV-2 antibodies among the general population in Belgium increased significantly from 25.2% in the first period (March 2021, week 13–14) to 78.1% in the last period (July 2021, week 26–27). A previous study, conducted after the first national lockdown in Belgium, showed a seroprevalence of 4.2% in October 2020 [ 22 ]. Furthermore, just before the launch of the vaccination campaign in January 2021, seroprevalence studies among Belgian blood donors [ 12 ] and primary health care workers [ 12 ] described a seroprevalence of 18.7% and 15.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated an average seroprevalence of 17.1% in residents and staff from NH across the Flemish region in the period mid-October to mid-November. This is higher than the seroprevalence of 9.2% in blood donors in the general Belgian population at the end of October 2020 [4,5], increasing to 13.6% by November, 11th [4].…”
Section: The Seroprevalence In Nh In Flanders In Fall 2020 Was Higher...mentioning
confidence: 95%
“…However, the reports on seroprevalence results, based on samples before 2021 (before the start of the vaccination campaign), are limited. The available results [4,5], revealed that, the percentage of blood donors (as a proxy for the general Belgian population) with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies was increasing from 5.0% (end of April 2020) up to 9.2% by the end of October 2020. For hospital staff [4,6,7], the seroprevalence was varying between 7.7% (end of April 2020) and 10.8% (end of October 2020).…”
Section: Introductionmentioning
confidence: 99%